Association of ambient PM2.5 and its components with preeclampsia risk among pregnant women in a high-altitude region - Rui Li; Zhenjuan Li; Hanping Ma; Donghua Li; Xiong Yue; Xiaoshu Zhang; Tingrong Wang; Zixuan Zou; Tianshan Shi; Xiaowei Ren (Environmental Pollution, 2026)

A machine-vision based seedling replenishing system for pepper plug seedling transplanter - Meng Chen; Yang Xu; Changjie Han; Panpan Yuan; Zhai Shi; Jia You; Desheng Li; Xu Ma; Hanping Mao (Computers and Electronics in Agriculture, 2026)

The Effects of Interactions Between Key Environmental Factors on Non-Specific Indicators in Carassius auratus - Bin Wang; Hang Yang; Hanping Mao; Qiang Shi (Fishes, 2025)
Carassius auratus exhibits significant physiological and behavioral alterations under the combined stress of temperature and dissolved oxygen (DO) fluctuations, which are common challenges in aquaculture. In this investigation, we employed controlled thermal and DO gradients to characterize the multidimensional response profile of this species. The key findings revealed that thermal elevation profoundly influenced blood glucose and cortisol concentrations. Notably, exposure to hyperoxic conditions markedly attenuated stress responses relative to hypoxia at equivalent temperatures: cortisol levels were significantly suppressed (reductions of 60.11%, 118.06%, and 34.72%), while blood glucose levels exhibited concurrent increases (16.42%, 26.43%, and 26.34%). Distinctive behavioral patterns, including floating head behavior, surface swimming behavior, and rollover behavior, were identified as indicative behaviors of thermal–oxygen stress. Molecular analysis demonstrated the upregulated expression of stress-associated genes (HSP70, HSP90, HIF-1α, and Prdx3), which correlated temporally with elevated cortisol and glucose concentrations and the manifestation of stress behaviors. Furthermore, a muscle texture assessment indicated that increased DO availability mitigated the textural deterioration induced by heat stress. Collectively, this work establishes an authentic biomarker framework, providing crucial threshold parameters essential for the development of intelligent, real-time environmental monitoring and dynamic regulation systems to enhance climate-resilient aquaculture management.

Associations of ambient air pollution exposure to fine particulate matter and its chemical constituents before and during pregnancy with the risk of full-term small for gestational age: a retrospective cohort study - Tingrong Wang; Hanping Ma; Rui Li; Donghua Li; Tianshan Shi; Zhenjuan Li; Zixuan Zou; Xiaowei Ren (International Archives of Occupational and Environmental Health, 2025)

Prenatal exposure to fine particulate matter chemical constituents and the risk of stillbirth and the mediating role of pregnancy complications: A cohort study - Tianshan Shi; Hanping Ma; Donghua Li; Li Pan; Tingrong Wang; Rui Li; Xiaowei Ren (Chemosphere, 2024)

Association of systemic inflammation with the obesity paradox in cancer: results from multi-cohort studies - Hailun Xie; Lishuang Wei; Heyang Zhang; Guotian Ruan; Xiaoyue Liu; Shiqi Lin; Jinyu Shi; Chenan Liu; Xin Zheng; Yue Chen; Hanping Shi (Inflammation Research, 2024)

Calibration and measurement of micrometre-scale pollen particles for discrete element method parameters based on the Johnson-Kendal-Roberts model - Qiang Shi; Bin Wang; Hanping Mao; Yong Liu (Biosystems Engineering, 2024)

Nutrition in Alzheimer’s disease: a review of an underappreciated pathophysiological mechanism - Jiwei Jiang; Hanping Shi; Shirui Jiang; Anxin Wang; Xinying Zou; Yanli Wang; Wenyi Li; Yuan Zhang; Mengfan Sun; Qiwei Ren; Jun Xu (Science China Life Sciences, 2023)

Influences of Aquaponics System on Growth Performance, Antioxidant Parameters, Stress Parameters and Gene Expression of Carassius auratus - Hanping Mao; Bin Wang; Jian Zhao; Yafei Wang; Xiaoxue Du; Qiang Shi (Fishes, 2023)
Aquaponics is a new type of composite farming system, which combines aquaculture and hydroponics through ecological design to achieve scientific synergism. However, the effects of aquaponics on the welfare status and stress parameters of fish are unclear. In this study, 150 crucian carp with an average initial body weight of 7.06 ± 0.32 g were selected. Nine fish were randomly selected as the control group (NC group and hypoxia group) for stress, antioxidant and gene expression parameters after acclimation and hypoxia stress, respectively. The remaining crucian carps were randomly divided into three experimental groups with 20 crucian carps in each group (T0, T1 and T2, respectively), with three replicates. The fresh weight of the lettuce root in the T2 group had no significant effect (p > 0.05). Compared with the control group (T0 and T1), there were significant differences in the specific growth rate, the weight gain rate, the fresh leaf weight, the chlorophyll content and the water quality parameters in group T2 (p

Ensemble learning system to identify nutritional risk and malnutrition in cancer patients without weight loss information - Liangyu Yin; Jie Liu; Ming Liu; Jin Zheng; Aiguo Xu; Quanjun Lyu; Yongdong Feng; Zengqing Guo; Hu Ma; Jipeng Li; Zhikang Chen; Hui Wang; et al. (Science China Life Sciences, 2023)

Comprehensive comparison of the prognostic value of systemic inflammation biomarkers for cancer cachexia: a multicenter prospective study - Hailun Xie; Guotian Ruan; Lishuang Wei; Heyang Zhang; Yizhong Ge; Qi Zhang; Shiqi Lin; Mengmeng Song; Xi Zhang; Xiaoyue Liu; Ming Yang; Meng Tang; et al. (Inflammation Research, 2022)

The combination of metabolic syndrome and inflammation increased the risk of colorectal cancer - Tong Liu; Yali Fan; Qingsong Zhang; Yiming Wang; Nan Yao; Mengmeng Song; Qi Zhang; Liying Cao; Chunhua Song; Hanping Shi (Inflammation Research, 2022)
Background Inflammation and metabolic syndrome (MetS) may act synergistically and possibly accelerate the initiation and progression of colorectal cancer (CRC). We prospectively examined the joint effect of MetS and inflammation on the risk of CRC. Methods We studied 92,770 individuals from the Kailuan study. MetS was defined based on the presence of three or more of the following components. (1) high glucose: FPG > 5.6 mmol/L; (2) high blood pressure: SBP ≥ 130 mmHg or DBP ≥ 85 mmHg; (3) high triglycerides: triglycerides > 1.69 mmol/L; (4) low HDL-C: HDL-C < 1.04 mmol/L in men or 1.29 mmol/L in women; and (5) visceral adiposity: waist circumference ≥ 85 cm in men or 80 cm in women. Inflammation was defined as hs-CRP ≥ 3 mg/L. We divided participants into four groups for the primary exposure according to the presence/absence of inflammation and presence/absence of MetS. Cox proportional hazards regression models were used to evaluate the association of MetS and/or inflammation with the risk of CRC. Results Compared with metabolically healthy noninflammatory individuals, inflammatory participants without MetS and inflammatory participants with MetS were associated with a 1.3-fold and 4.18-fold increased risk of CRC with corresponding HRs (95% CI) of 1.34 (1.09, 1.64) and 4.18 (3.11, 5.62), respectively. The combination of MetS and inflammation was associated with the highest risk of CRC in all subgroups, especially among participants who were female, in younger age, and obese. Sensitivity analyses further validated our primary findings. Conclusions We found the combination of MetS and inflammation could significantly increase the risk of CRC. Including CRP in the diagnosis of MetS may help to identify additional high-risk participants who should be targeted for early diagnosis and prevention of CRC. Trial registration Kailuan study, ChiCTR–TNRC–11001489. Registered 24 August, 2011-Retrospectively registered, http:// www.chictr.org.cn/showprojen.aspx?proj=8050

Effects of Different Temperatures on the Antibacterial, Immune and Growth Performance of Crucian Carp Epidermal Mucus - Bin Wang; Guoxin Ma; Yong Liu; Yafei Wang; Xiaoxue Du; Qiang Shi; Hanping Mao (Fishes, 2021)
Fish is one of the important sources of energy and protein, and proper water temperature is key to successful fish breeding. The authors of this study evaluated crucian carp growth, mucus antibacterial properties, and immune indicators at 17, 21, 24, 27, and 31 °C. The results indicated that in the range of 17–31 °C, the resistance of epidermal mucus to Vibrio harveyi decreased with temperature rising. At 24 and 27 °C, the activities of lysozyme and catalase significantly increased; alkaline phosphatase activity, superoxide dismutase activity, and total protein concentration first increased and then decreased with rising temperature; the highest values were observed at 24 °C, with increases of 56.55%, 26.64%, and 44.52%, respectively, compared to those under the 17 °C treatment. When the treatment reached 27 °C, the temperature had an effect on the growth and antibacterial properties of crucian carp, and the activities of alkaline phosphatase and superoxide dismutase were significantly reduced. At temperatures of 17–24 °C, the survival rate of crucian carp could reach more than 93%, and at the temperature of 24 °C, the specific growth rate reached the highest value of 43.29%. Therefore, the most favorable temperature for the long-term breeding of crucian carp was found to be 24 °C. This study provides a favorable experimental basis for the establishment of intelligent aquaculture systems and the setting of water environment parameters.

Nutrition status of patients with common cancer in China: gap, mission and challenge - Chunlei Hu; Qi Zhang; Hanping Shi (Science China Life Sciences, 2021)

Correlations between 13 Trace Elements and Circulating Tumor Cells in Patients with Colorectal Cancer in Guangzhou, China - Hetao Wang; Hao Liu; Meijuan Zhou; Hanping Shi; Mei Shen (Biological Trace Element Research, 2020)

Transient receptor potential vanilloid-3 (TRPV3) activation plays a central role in cardiac fibrosis induced by pressure overload in rats via TGF-β1 pathway - Yan Liu; Hanping Qi; Mingyao E; Pilong Shi; Qianhui Zhang; Shuzhi Li; Ye Wang; Yonggang Cao; Yunping Chen; Lina Ba; Jingquan Gao; Wei Huang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Influence of NH3/CO2 Modification on the Characteristic of Biochar and the CO2 Capture - Zhang Xiong; Zhang Shihong; Yang Haiping; Shi Tao; Chen Yingquan; Chen Hanping (BioEnergy Research, 2013)